High occurrence of enterotoxigenic isolates and low antibiotic resistance rates of Staphylococcus aureus isolated from raw milk from cows and ewes. (9th May 2019) - Khemiri, M.; Abbassi, M.S.; Elghaieb, H.; Zouari, M.; Dhahri, R.; Pomba, C.; Hammami, S.
Abstract: This study aimed to analyse the frequency of genes encoding virulence factors and to characterize resistance profiles of Staphylococcus aureus isolated from raw milk. In total, 47 and 9 S. aureus isolates were recovered from 150 and 100 raw bovine and ovine milk samples, respectively, in Tunisia. The majority of isolates was resistant to penicillin, and no methicillin‐resistant S. aureus was detected. Eighteen and two isolates harboured etd and eta genes respectively. Sixteen enterotoxin‐encoding genes were detected ( n, %): sed (25, 44·6%), sec (16, 28·6%), sei (16, 28·6%), seh (13, 23·2%), seln (13, 23·2%), sell (10, 17·8%), seg (9, 16%), selu (8, 14·3%), selq (7, 12·5%), selo (7, 12·5%), selm (7, 12·5%), seb (7, 12·5%), sea (6, 10·7%), selk (3, 5·4%), ser (1, 1·8%) and selp (1, 1·8%). Ten isolates carried the tsst1 gene. All isolates carried the haemolysin toxin ( hla, hld and hlg ). The immune evasion cluster system‐type B was predominant (20 isolates) followed by C (3 isolates), A and E (1 isolate each). The occurrence of enterotoxigenic S. aureus in raw milk constitutes a potential risk for human health. Significance and Impact of the Study: This paper describes the characteristics of Staphylococcus aureus isolated from raw milk samples from healthy cows and ewes collected from small family farms in Tunisia. Fifty‐six strains were analysed by determining their antibiotic susceptibility and genes encoding antibiotic resistance and virulence factors. Methicillin‐resistant strains were not detected, and overall low level of antimicrobial resistance was reported. However, our strains harboured several genes encoding virulence factors and 87·5% of them carried at least one gene encoding for enterotoxins showing a high risk of spread of food‐borne diseases. Abstract : Significance and Impact of the Study: This paper describes the characteristics of Staphylococcus aureus isolated from raw milk samples from healthy cows and ewes collected from small family farms in Tunisia. Fifty‐six strains were analysed by determining their antibiotic susceptibility and genes encoding antibiotic resistance and virulence factors. Methicillin‐resistant strains were not detected, and overall low level of antimicrobial resistance was reported. However, our strains harboured several genes encoding virulence factors and 87·5% of them carried at least one gene encoding for enterotoxins showing a high risk of spread of food‐borne diseases.